Equivalence of Definitions of Trigonometric Series
Jump to navigation
Jump to search
Theorem
The following definitions of the concept of Trigonometric Series are equivalent:
Conventional Form
A trigonometric series is a series of the type:
- $\map S x = \dfrac {a_0} 2 + \ds \sum_{n \mathop = 1}^\infty \paren {a_n \cos n x + b_n \sin n x}$
where:
- the domain of $x$ is the set of real numbers $\R$
- the coefficients $a_0, a_1, a_2, \ldots, a_n, \ldots; b_1, b_2, \ldots, b_n, \ldots$ are real numbers independent of $x$.
Complex Form
A trigonometric series can be expressed in a form using complex functions as follows:
- $\map S x = \ds \sum_{n \mathop = -\infty}^\infty c_n e^{i n x}$
where:
- the domain of $x$ is the set of real numbers $\R$
- the coefficients $\ldots, c_{-n}, \ldots, c_{-2}, c_{-1}, c_0, c_1, c_2, \ldots, c_n, \ldots$ are real numbers independent of $x$
- $c_{-n} = \overline {c_n}$ where $\overline {c_n}$ is the complex conjugate of $c_n$.
Proof
Let $\map S x = \dfrac {a_0} 2 + \ds \sum_{n \mathop = 1}^\infty \paren {a_n \cos n x + b_n \sin n x}$.
Set:
\(\ds \cos n x\) | \(=\) | \(\ds \frac {e^{i n x} + e^{- i n x} } 2\) | Euler's Cosine Identity | |||||||||||
\(\ds \sin n x\) | \(=\) | \(\ds \frac {e^{i n x} - e^{- i n x} } {2 i}\) | Euler's Sine Identity |
Then:
\(\ds \map S x\) | \(=\) | \(\ds \dfrac {a_0} 2 + \sum_{n \mathop = 1}^\infty \paren {a_n \frac {e^{i n x} + e^{- i n x} } 2 + b_n \frac {e^{i n x} - e^{- i n x} } {2 i} }\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \dfrac {a_0} 2 + \sum_{n \mathop = 1}^\infty \paren {\paren {\frac {a_n} 2 + \frac {b_n} {2 i} } e^{i n x} + \paren {\frac {a_n} 2 - \frac {b_n} {2 i} } e^{- i n x} }\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \dfrac {a_0} 2 + \sum_{n \mathop = 1}^\infty \paren {\paren {\frac {a_n - i b_n} 2} e^{i n x} + \paren {\frac {a_n + i b_n} 2} e^{- i n x} }\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \dfrac {a_0} 2 + \sum_{n \mathop = 1}^\infty \paren {\frac {a_n - i b_n} 2} e^{i n x} + \sum_{n \mathop = 1}^\infty \paren {\frac {a_n + i b_n} 2} e^{- i n x}\) |
Let $b_0 := 0$.
Then let:
- $\forall n \in \N: c_n = \dfrac {a_n - i b_n} 2$
Thus it follows that:
- $c_0 = \dfrac {a_0 - 0 \times i} 2 = \dfrac {a_0} 2$
Then let:
- $c_{-n} = \dfrac {a_n + i b_n} 2$
from which it follows that:
- $c_{-n} = \overline {\paren {\dfrac {a_n - i b_n} 2} }$
and again:
- $c_0 = \dfrac {a_0 + 0 \times i} 2 = \dfrac {a_0} 2$
Then it is noted that:
- $e^{i \times 0 \times x} = e^0 = 1$
and it follows that:
\(\ds \map S x\) | \(=\) | \(\ds \frac {a_0} 2 + \sum_{n \mathop = 1}^\infty \paren {\frac {a_n - i b_n} 2} e^{i n x} + \sum_{n \mathop = 1}^\infty \paren {\frac {a_n + i b_n} 2} e^{- i n x}\) | from above | |||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{n \mathop = 0}^\infty \paren {\frac {a_n - i b_n} 2} e^{i n x} + \sum_{n \mathop = 1}^\infty \paren {\frac {a_n + i b_n} 2} e^{- i n x}\) | subsuming $a_0$ into first summation | |||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{n \mathop = 0}^\infty c_n e^{i n x} + \sum_{n \mathop = 1}^\infty c_{-n} e^{- i n x}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{n \mathop = 0}^\infty c_n e^{i n x} + \sum_{n \mathop = -\infty}^{-1} c_n e^{i n x}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{n \mathop = -\infty}^\infty c_n e^{i n x}\) |
where it is noted that $c_{-n} = \overline {c_n}$ as required.
$\blacksquare$
Sources
- 1961: I.N. Sneddon: Fourier Series ... (previous) ... (next): Chapter One: $\S 1$. Trigonometrical Series